Analysis of the Influence of Financial Flexibility, Financial Distress, and Tax Policies on the Performance of Companies on the Indonesia Stock Exchange - Erin Erin; Yuniarwati Yuniarwati (Eduvest - Journal of Universal Studies, 2025)
The growth of Indonesia's manufacturing sector GDP has shown a declining trend since 2016 and was further exacerbated by the Covid-19 pandemic, necessitating improved company performance through the application of sound financial management principles. Financial flexibility, financial distress, and tax policies are key factors that need to be studied to understand their impact on the performance of manufacturing companies. This study aims to identify the influence of financial flexibility, financial distress, and tax policies on the performance of manufacturing companies in Indonesia.bThis research uses a quantitative method with a descriptive statistical approach, examining manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023. A sample of 123 companies was selected using purposive sampling techniques, and data analysis was used to test the analysis hypothesis, namely panel data regression using the Eviews 12 program to broadcast the influence of financial flexibility, financial difficulties and tax policy on company performance. The research results show that financial flexibility has no significant effect on company performance and financial distress has a significant effect on company performance, while tax policy has a significant effect on company performance.